2014
DOI: 10.12659/msmbr.889811
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of carbapenem and aminoglycoside resistance genes among multidrug-resistant clinical isolates of Acinetobacter baumannii from Cracow, Poland

Abstract: BackgroundAcinetobacter baumannii is a significant hospital pathogen, possessing a considerable degree of antimicrobial resistance. A. baumannii resistance to carbapenems and aminoglycosides is mostly conferred by class D OXA carbapenemases and aminoglycoside-modifying enzymes, respectively. The aim of this study was to determine the prevalence of selected genes encoding OXA carbapenemases and aminoglycoside-modifying enzymes in multidrug-resistant strains of A. baumannii.Material/MethodsThe study included 61 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…However, 89.4% of our isolates containing this gene showed an MIC range of ≥256 µg/mL for spectinomycin, streptomycin, kanamycin, and tobramycin, while 100% of them exhibited this MIC range for gentamicin. Moreover, according to research by Hasani et al, this gene was detected in SG1-4 1 , while Nowak et al did not detect this gene among their isolates 28 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, 89.4% of our isolates containing this gene showed an MIC range of ≥256 µg/mL for spectinomycin, streptomycin, kanamycin, and tobramycin, while 100% of them exhibited this MIC range for gentamicin. Moreover, according to research by Hasani et al, this gene was detected in SG1-4 1 , while Nowak et al did not detect this gene among their isolates 28 .…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, 74% and 88.3% of our isolates containing aphA6 exhibited MIC values of ≥256 µg/mL for amikacin and kanamycin, respectively. Moreover, a study carried out in Poland revealed that aphA6 was the second most prevalent AME gene (78.7%) among 61 A. baumannii isolates 28 . However, aadB, the second most prevalent AME gene in the current study, confers resistance to gentamicin, tobramycin, and kanamycin in gram-negative bacteria 26 , while 95.8%, 93.1%, and 87.6% of our isolates containing aadB showed an MIC range of ≥256 µg/mL for these antibiotics, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a paucity of data regarding the aac(3)-IIa gene distribution in A. baumannii . It was reported that only 4 strains (3.7%) carried aac(3)-IIa genes (62); aac(3)-IIa was not identified in any strains in a study by Nowak et al (63). Previous studies have reported that aac(3)-IIa modifies gentamicin, which explains the observed high rate of resistance to gentamicin in these A. baumannii strains (59).…”
Section: Discussionmentioning
confidence: 98%
“…The aminoglycoside-resistant gene aphA6 was reported in Egypt [ 17 ]. On a more international scale, the following aminoglycoside-resistant genes were reported in Poland in 2013: aphA1 , aphA6, and aacC1 [ 18 ]. Our isolates are equipped with not only enzymatic resistance mechanisms, but also the ompA biofilm-producing virulence factor.…”
Section: Discussionmentioning
confidence: 99%